Laments on Death by Alevis and Bektashis of Pazarcık Region - Pehlivan, Fatih Furkan (Journal of Alevism-Bektashism Studies, 2023)
The most crucial elements that keep nations standing and ensure their eternal existence are their cultural values. Our foremost responsibility is to preserve and pass on our cultural values to the future. Our tradition of lamentation, which consists of vivid and poignant expressions of humanity’s shared and irremediable sorrows, has initially recorded the pain and subsequently nourished the cultural fabric of the nation as an accumulation of melodies spanning thousands of years.This research holds significance in aiming to make various observations about the characteristics of the Alevi and Bektashi lament tradition in the Kahramanmaraş-Pazarcık region. It is intended to be a valuable resource contributing to global cultural studies, safeguarding our country’s national and spiritual values, and making a contribution to the field of musicology while ensuring the transfer of the region’s cultural characteristics to future generations. The Alevi and Bektashi lament tradition in the Kahramanmaraş-Pazarcık region involves making various observations about the stories of laments, notation of laments, and detailed features related to laments to determine their status in the tradition. One of the research objectives is to examine and document the Alevi and Bektashi laments in the Kahramanmaraş-Pazarcık region, contributing to the preservation of the local culture for future generations and thus safeguarding our cultural values.The research begins with general information about laments, followed by documenting the stories and notations of some laments that occurred in Pazarcık. A digital and written source scan was conducted to identify the works. The research is limited to the Alevi and Bektashi laments of Pazarcık. Personal interviews with lament singers and their close circles provided detailed insights during the research process. The findings of the research and examinations reveal that the Alevi and Bektashi communities in the Kahramanmaraş-Pazarcık region have distinctive characteristics. The lament tradition of the region shares similar features with lament traditions in other parts of our country. It is observed that they generally prefer unaccompanied, simple vocals while performing laments and often address incidents encountered in their daily lives as the subject matter of their works.
Keywords: Alevism; Bektashism; Death; Mourning; Lament; Pazarcık